Shear strengthening and repair of deep beams with and without web reinforcement using near-surface mounted CFRP bars - Raheem Hassan, Douread (2018)
Shear failure of a reinforced concrete beam is catastrophic because it occurs suddenly and without warning. Recently, CFRP sheets and bars have been rapidly employed in strengthening structural concrete elements including deep beams. In this research, the behaviour of deep beam strengthened with carbon fiber reinforced polymer (CFRP) as Near Surface Mounted (NSM) bars was studied. Five groups of deep beams i.e. G1, G2, G3, G4 and G5 were studied. Each group of deep beams has the same shear span to effective depth ratio at 0.864. Group G1 consists of two beams as a control specimens and each one differs depending on either with web and without web reinforcement. Groups G2 to G5 consists of initially strengthened or pre-cracked and repaired deep beams with CFRP NSM bars with different schemes and orientations. Other variables included beams with and without web reinforcements. The selected orientations for all CFRP NSM bars were either at 0/90 or 45/135 degrees and the two different spacing schemes for the stirrups were at 100 mm or 150 mm. In total, 18 reinforced concrete deep beams with a size of 450 x140 x1200 mm were experimented. A simulation using finite element software ANSYS V.14 was conducted to validate the experimental work. Three existing theoretical equations from ACI 440, Khalifa & Nanni and fib were selected for comparison with the experimental findings. From the experimental, all deep beam specimens failed in shear. Experimental results indicated that all deep beams, either with or without web reinforcement, and strengthened or repaired with CFRP NSM bars showed increased shear capacity enhancement from 17% to 141% compared to the control specimens. Finite element analysis by ANSYS software also indicated similar behaviour in terms of shear capacity, crack patterns and mode of failure. In addition, three existing theoretical models; ACI 440, Khalifa and Nanni and fib models were applied for theoretical comparison of shear capacity contributed by CFRP NSM bars Vf . The ACI 440 and Khalifa & Nanni model showed good consistency and good agreement with the experimental results. Finally, a modified effective strain limit based on different coefficient (R) values was proposed.